Refleksi Nilai Kearifan Lokal (Local Wisdom) dalam Pembelajaran Sains Sekolah Dasar: Literature Review - Aisa Nikmah Rahmatih; Mohammad Archi Maulyda; Muhammad Syazali (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2020)
Local wisdom of Sasak society is a system of life and values of the Sasak ethnic group, since the past, has proven to give meaning if applied teguq, tuhu, bender and trasna in society. The value of local wisdom is supported by the existence of awik-awik or dynamic customary rules. Awik-awik contains contextual values according to the region of each region which is related in science learning of elementary school students. Through qualitative methods and literature reviews, the author tries to explore the reflection of the value of local wisdom in learning science. In awik-awik the characteristics of science / science are reflected in the form of products, processes and attitudes. Linking awik-awik in learning science aims to instill a sense of love for the noble values of culture and students get real learning experiences and their surroundings. This is expected to motivate teachers to implement it in the design of learning in schools